2020
DOI: 10.1002/qre.2726
|View full text |Cite
|
Sign up to set email alerts
|

Design of a variable sampling interval exponentially weighted moving average median control chart in presence of measurement errors

Abstract: In the literature, many control charts monitoring the median is designed under a perfect condition that there is no measurement error. This may make the practitioners confusing to apply these control charts because the measurement error is the true problem in practice. In this paper, we consider the effect of measurement error on the performance of the exponentially weighted moving average (EWMA) control chart combining with the variable sampling interval (VSI) strategy. A linear covariate error model is suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…A linear covariate error model was put forth by 1 when control charts with measurement error were taken into account. In recent years, numerous scholars have employed this paradigm extensively; see 2,3,4,5,6,7,8 . All of these studies showed that measurement error had a negative impact on the performances of control charts, making control charts perform worse.…”
Section: Introductionmentioning
confidence: 99%
“…A linear covariate error model was put forth by 1 when control charts with measurement error were taken into account. In recent years, numerous scholars have employed this paradigm extensively; see 2,3,4,5,6,7,8 . All of these studies showed that measurement error had a negative impact on the performances of control charts, making control charts perform worse.…”
Section: Introductionmentioning
confidence: 99%
“…Saccucci et al (1992) developed the VSI EWMA chart for the process mean, and they demonstrated that the developed chart outperforms the VSI CUSUM chart in detecting small shifts, as well as the VSI SH and non-adaptive EWMA charts in detecting all sizes of shifts. Recent studies on control charts with the VSI approach include those by Haq et al (2021), Tran et al (2021), Nguyen et al (2021), Umar et al (2021), Haq, Sadia, and Khoo (2022) and Haq and Khoo (2022a).…”
Section: Introductionmentioning
confidence: 99%
“…Next, Maravelakis et al (2004) and Maravelakis (2012) investigated the effect of measurement errors on the EWMA and CUSUM schemes, respectively; with the effect of a two-component measurement error on the EWMA scheme investigated in Abbasi (2016). For some recent discussions on measurement errors published after the review paper of Maleki et al (2017), see for instance Asif et al (2020), Cheng and Wang (2018), Nguyen et al (2019), Noor-ul-Amin et al (2020), Riaz et al (2019), Sabahno et al (2019, 2020), Salmasnia et al (2018), Shongwe et al (2020a, b, c), Tang et al (2019), Tran et al (2019a, b, c, 2020), Yeong et al (2017), Zaidi et al (2019, 2020).…”
Section: Introductionmentioning
confidence: 99%